PENGARUH KARAKTERISTIK ANAK, KEBERADAAN ORANG TUA, DAN POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN SOSIAL, EMOSIONAL DAN MORAL PADA USIA SEKOLAH WILAYAH KOTA DAN DESA DI KABUPATEN BANYUMAS - Sodikin Sodikin; Mustiah Yulistiani; Asiandi Asiandi (Sainteks, 2011)
ABSTRACT Understanding factors that control the behavior of children and properly manage children's behavior is an important part of development, particularly the social, emotional and moral development. This study aims to prove the allegation of the influence of the characteristics, the presence of parents, and foster pattern of parents to the social, emotional, and moral development on school age children in urban and rural areas in Banyumas Regency. The study design was cross sectional with a population of all school age children. Samples are school age children in urban and rural areas aged 10-12 years in Banyumas Regency. The sampling technique was purposive sampling, with a total sample of 350 (n = 350). The results showed the leading factors related to social, emotional, moral development of school age children in Banyumas Regency (magnitude more than 0.45) is father’s job/l ocation of school (first factor), mother’s job/school location (second factor), and foster pattern of parents (third factor). Eigen values showed 49% of the total item is determined by the first factor, 28% the second factor, and 73% the third factor. Factors that influence of social, emotional, and moral development of school age children in Banyumas Regency is school location in rural or urban (the factor of child characteristics), father’s job and mother’s job (the factor of the presence of parents), and the factor of foster pattern of parents. The results implication of this study suggest every parent worker should take into account the quality and quantity of contact with children so there were no social, emotional and moral problems in the future; parents should disseminate pro-social values to prevent children becoming aggressive, anti-social and oriented give sanction (sanction-oriented) to others; necessary to develop social and emotional learning competencies (five social and emotional competency learning) to the children include the development of self-awareness, social awareness, relationship skills, responsible decision making, and self-management. Keywords: social, emotional, and moral development, factor analysis